The determinants of tax revenue in Malaysia - Beh, Keah Kiang; Cheah, Hon Chiew; Chek, Wen Hao; Lim, Yong Foong (2021)
The purpose of this research paper is to study the determinants of tax revenue of Malaysia which are GDP per Capita, Inflation, Openness Level, Share of Manufacturing, Public Debt, and Foreign Direct Investment. We are using the annual data from the year 1989 to the year 2018. After we conduct unit root tests, we found that all of our time series data also have unit root (non-stationary) at their level form. Therefore, we use ARDL bound test and VECM test to examine the long-run relationship and causality relationship between our dependent variable and independent variables. The results show that there has a long-run relationship between Malaysia’s tax revenue and determinants of tax revenue. Moreover, public debt, openness level, and inflow of FDI have a positive impact on the tax revenue of Malaysia, while GDP per capita, inflation, and manufacturing have a negative impact on Malaysia’s tax revenue.